Opposing effects of oestradiol and progesterone on intracellular pathways and activation processes in the oxidative stress induced activation of cultured rat hepatic stellate cells. Issue 12 (13th July 2005) - Itagaki, T; Shimizu, I; Cheng, X; Yuan, Y; Oshio, A; Tamaki, K; Fukuno, H; Honda, H; Okamura, Y; Ito, S
Abstract : Background: Oxidative stress, including the generation of reactive oxygen species (ROS), is involved in hepatofibrogenesis. The authors' previous studies have shown that oestradiol suppresses hepatic fibrosis in animal models and attenuates the activation of cultured rat hepatic stellate cells (HSCs), which possess oestrogen receptor subtype β and are also activated by ROS. Aims: To define the mechanisms by which female sex hormones play an antifibrogenic role in activated HSCs, the effects of oestradiol and progesterone on ROS generation processes and intracellular pathways, leading to the activation of HSCs undergoing oxidative stress, was examined. Methods: HSCs, isolated from rats, were cultured for 7 days with oestradiol or progesterone for 24 hours as pretreatment, and oxidative stress was then induced by exposure to low doses of hydrogen peroxide for another 24 hours. Results: Oestradiol inhibited ROS generation and antioxidant enzyme loss via the suppression of NADH/NADPH oxidase activity, and attenuated hydrogen peroxide induced transforming growth factor-β1 (TGF-β1) expression, HSC proliferation and transformation, and the activation of mitogen activated protein kinase (MAPK) pathways and transcription factors. Progesterone exerted a stimulatory effect through the progesterone receptor on the induction of ROS generation processes and intracellular pathways, resulting in TGF-β1 expression and HSC activation, and fibrogenic effects were inhibited by oestradiol. Conclusion: These findings show for the first time that oestradiol inhibits the activation of transcription factors by suppressing ROS generation processes and the MAPK pathways, and inactivates the downstream transcription processes involved in TGF-β1 expression and HSC activation, whereas progesterone acts in opposition to the favourable effects of oestradiol and its effects are blocked by oestradiol.